In-situ S/TEM investigations of deformation and damage mechanisms in neutron-irradiated EUROFER97 - Qian Yuan; Ankur Chauhan; Lakshay Chauhan; Dimitri Litvinov; Ermile Gaganidze; Hans-Christian Schneider; Jarir Aktaa (Philosophical Magazine Letters)
In this work, we employed in-situ S/TEM techniques to investigate deformation and damage mechanisms in neutron-irradiated reduced-activation ferritic/martensitic (RAFM) EUROFER97 steel subjected to a dose of 15 dpa at 330 °C. The irradiated microstructure revealed uniformly distributed dislocation loops and sporadic nanometer-sized cavities. During in-situ straining of a focused-ion beam (FIB)-prepared lamella, mobile line dislocations were observed to interact with dislocation loops, leading to loop absorption and the formation of dislocation networks. Further straining resulted in the formation of a dislocation-loop-free zone. Within this region, deformation-induced nanometer-sized cavities emerged, likely from pre-existing irradiation-induced clusters, cavities, or remnants of absorbed loops. Coalescence of these cavities led to the formation of micro-cracks and ultimately to the fracture of the lamella. This suggests premature failure of the irradiated sample compared to its unirradiated counterpart, highlighting irradiation-induced embrittlement.